واقع تدريس مقرر التربية المهنية في مرحلة التعليم الأساسي من وجهة نظر معلمي المقرر وأمناء المشاغل في مدارس محافظة اللاذقية الرسمية - شيخ خميس، فاطمة الزهراء يوسف; أبو حمود، هيثم (الجامعة الأردنية - عمادة البحث العلمي, 2018)
The study aimed to identify the reality of teaching Prevocational Education course in primary education from the viewpoint of teachers and secretaries operator in the official schools in Latakia Governorate. The study sample consisted of all the Prevocational education teachers with total of (15) teachers, and all the secretaries operator with total of (15). The sample was selected intentionally during the second semester of the school during the period of 2014-2015. To achieve the study goal, two questionnaires were developed, one from the teachers contains (50) items assigned to six domains, the other from the secretaries operator contains (129) items assigned to seven domains, and the tool has been checked and verified. For data analysis the researcher used the following Tests same like means, standard deviations, t-test, One Way Analysis of Variance, MANOVA and Scheffe test. The results showed that the evaluation degree of Prevocational Education teachers about the reality of teaching Prevocational Education course was in a medium level, while the ones of secretaries operators were low. A high degree of correspondence between Prevocational education teachers and the secretaries operator. They also revealed that there were no significant differences due to the gender in the point of view of the teachers, while there were significant differences due to the specialization for manual design institution and craft teacher, and there were significant differences between the average estimate of the research in relation to the statue of operator, if it is ready to operate or the operator with lack of readiness. The study recommended the need to reconsider the teaching experience of Prevocational education course, and to include it within the study plan, and processing the Prevocational operators optimally.
هدفت الدراسة إلى التعرف لواقع تدريس مقرر التربية المهنية في مرحلة التعليم الأساسي من وجهة نظر معملي المقرر وأمناء المشاغل في مدارس محافظة اللاذقية الرسمية. تكون مجتمع الدراسة وعينته من جميع معلمي التربية المهنية والبالغ عددهم (15) معلما ومعلمة، وجميع أمناء المشاغل والبالغ عددهم (15) أمينا تم اختيارهم بطريقة قصدية خلال الفصل الدراسي الثاني للعام الدراسي (2014-2015)، ولتحقيق هدف الدراسة تم بناء استبانتين إحداهما وجهت للمعلمين مكونة من (50) فقرة موزعة على ستة مجالات، وجهت الاستبانة الأخرى لأمناء المشاغل وهي مكونة من (129) فقرة موزعة على سبعة مجالات، وتم التحقق من صدق الأداتين وثباتهما. ولتحليل نتائج الدراسة استخدمت الباحثة المعالجات الإحصائية كالمتوسطات الحسابية والانحرافات المعيارية، واختبار (ت)، وتحليل التباين الأحادي، وتحليل التباين المتعدد واختبار شيفيه. أظهرت نتائج الدراسة أن درجة تقدير معلمي التربية المهنية حول واقع تدريس المقرر جاءت بمستوى متوسط، بينما جاءت درجة تقدير أمناء المشاغل بمستوى منخفض. وبلغت درجة التطابق بين تقدير المعلمين وتقدير أمناء المشاغل بمستوى منخفض. وبلغت درجة التطابق بين تقدير المعلمين وتقدير أمناء المشاغل مستوى مرتفع. وأظهرت الدراسة أيضا عدم وجود فروق ذات دلالة إحصائية بين متوسط تقدير أفراد عينة الدراسة على استبانة المعلمين حول واقع تدريس مقرر التربية المهنية تعزي لمتغير الجنس، ووجود فروق ذات دلالة إحصائية تعزى لمتغير التخصص لصالح تخصص معهد الإعداد اليدوي وتخصص معلم الحرفة، ووجود فروق ذات دلالة إحصائية بين متوسط تقدير أفراد عينة الدراسة على استبانة أمناء المشاغل تعزى لمتغير حالة المشغل لصالح المشغل المجهز والمشغل ناقص التجهيز. أوصت الدراسة بضرورة إعادة النظر في تجربة تدريس مقرر التربية المهنية، وإدخالها ضمن الخطة الدراسية حتى تحظى بالاهتمام الكافي، وتجهيز مشاغل التربية المهنية بالشكل الأمثل.
Keywords: التعليم الأساسي -- التربية المهنية -- معلمو التربية المهنية -- المقررات الدراسية